Pengetahuan dan Skil Pekerja Sosial Kesihatan Mental di Malaysia - Ahmad Ramli, Fatimah Zailly; Yusof, Yusmarhaini; Mohd Noor, Norfarahin (UUM Press, 2016)
Knowledge's and skills in providing documentation, client assessment and problems solving based on theories and relevance methods are essential roles in the social work profession. The ability to conduct psycho social assessment among clinical social workers are particularly important in mental health for social work to help clients to overcome their problems. Face to face interviews were conducted with respondents working in mental health setting. Semi- structured interview was utilized to identify the knowledge and skills required for a mental health social worker. Respondents’ transcription were analysed using thematic analysis based on the research objectives. Findings showed that elements of knowledge's and skills required by social workers in mental health setting could be categorized into four components: (i) knowledge in doing assessment; (ii) knowledge about mental health and the competencies in relevant theories; (iii) knowledge on academic qualification and advanced social work training and (iv) additional skills as a social worker in a mental health setting.